Time Consistent Policy and the Structure of Taxation - Neil Bruce (Queen's University, Department of Economics, 1990)
It is now well known that "optimal" government policies may not be time consistent–that is, ex post optimal. Time consistency considerations can be shown to reverse the conclusions about the relative merits of different tax structures that are drawn from Ramsey type analysis. In this paper I show with the help of a simple overlapping generations model that this is the case for the "presumption" that direct taxes, for which tax rates can be made contingent on household characteristics, weakly dominate indirect taxes, which are levied on transactions. The ability of the government, with direct taxation, to levy different tax rates on households in different periods of their life-cycles introduces a time consistency problem that is not present with the "anonymous" tax rates levied under indirect taxation.
Keywords: 330; time consistency; direct and indirect taxation; overlapping generations